2023
DOI: 10.1007/s11356-022-24752-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical additives and mature compost on reducing nitrogen loss during food waste composting

Abstract: This study aims to investigate the effect of adding different types of mature compost amendments and sulfur powder on nitrogen loss and compost maturity of food waste. High-throughput sequencing was used to analyze the bacterial community during composting. Results showed that the secondary fermentation mature compost mixed with sulfur powder group had the most reduction of ammonia emission (56.3%) and the primary fermentation mature compost amendments were the most effective for nitrous oxide emission reducti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The NH 3 emission could be ascribed to the intensive mineralization of organic nitrogen to NH 4 + , which was further transformed into NH 3 under high temperature and alkaline conditions ( Xiong et al, 2023 ). As the composting processed, the NH 3 emission showed a trend of first rising and then falling ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NH 3 emission could be ascribed to the intensive mineralization of organic nitrogen to NH 4 + , which was further transformed into NH 3 under high temperature and alkaline conditions ( Xiong et al, 2023 ). As the composting processed, the NH 3 emission showed a trend of first rising and then falling ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…The nitrate nitrogen content of all groups gradually increased in composting ( Figure 2D ). Considering that the activity of nitrifying bacteria is easily affected by temperature ( Xiong et al, 2023 ), nitrification is inhibited in the mesophilic and thermophilic stages, resulting in the mainly production of nitrate nitrogen in the later stage of composting. The nitrate nitrogen content of V150 with continuous aeration was higher than the other treatments on days 2 ~ 7 of composting and reached a maximum value of 5.33 g/kg by the end of composting.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical additives are added to the pile to provide immobilization, reduce gas emissions, and regulate the physicochemical properties of the pile [ 182 ]. Xiong et al added sulfur powder and mature compost to the compost and showed a maximum reduction of 56.3% in NH 3 emissions and a reduction in N 2 O emissions (36.9%) by the synergistic effect of the two [ 183 ]. Liu et al added calcium-magnesium phosphorus, biochar, and mushroom substrate to the compost.…”
Section: Factors Affecting Composting Of Aow Waste and Its Regulationmentioning
confidence: 99%